Self Defense Yang Dilakukan Oleh Amerika Serikat Terhadap Jenderal Soleimani Dalam Prespektif Hukum Internasional - Adwiyah, Aiin Widya Rhabiatul; Anwar, Arman; Wattimena, Josina Augustina Yvonne (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2022)
Introduction: The use of armed force is generally prohibited under international law, and is permitted only in two exceptions, namely when a country acts in selfdefense or when the United Nations gives it the right to respond to acts of aggression. Purposes of the Research: This study will examine the legitimacy of the use of armed force in the implementation of self-defense, and whether the use of self-defense by America is in accordance with the concept of self-defense regulated in international law. Methods of the Research: This research is a normative legal research, using a descriptive analytical research type using primary, secondary, and tertiary legal materials. The approach used is the statutory approach, the conceptual approach, and the case approach. The technique of collecting legal materials uses a literature study which is then analyzed qualitatively to answer the problems studied. Results Originality of the Research: The legality of the use of armed force in the right to self-defense is regulated in article 51 of the UN charter provided that an armed attack has occurred first, and must be reported to the UN Security Council beforehand. The concept of self-defense that America did to General Soleimani was not in accordance with the provisions in article 51 of the charter. In addition, America violated the laws of war because attacks were carried out in peacetime and targeted killings of certain commanders of a country violated human rights.